Effects of a rework program in a university hospital and predictors of work restoration and maintenance in the participants - Yamashita, Hitomi; Sakai, Akari; Terao, Takeshi (Frontiers in Psychiatry, 2022)
During sickness absence, it appears necessary for psychiatric patients suffering from depression or bipolar disorder to undergo a psychiatric rehabilitation called the rework program that aids in work restoration and maintenance. However, few studies have investigated the effects of such a program and predictors of work restoration and maintenance in the participants. Here, we aimed to investigate the effects of a rework program as well as to examine whether cognitive function and mental state at the end of the rework program predict the probability of work restoration and maintenance and whether the frequency of rework program participation predicts successful work restoration and maintenance. The rework program included both patients absent from work and unemployed patients. Patients completed assessments including Trail Making Test Type B (TMT-B), the Wisconsin Card Sorting Test, and the Social Adaptation Self-Evaluation Scale just before graduating from the rework program. Simultaneously, their depressive state was assessed using the Hamilton Depression Rating scale. The patients were divided into the job group, comprising 90 patients who were able to restore their work or get a new job, and the non-job group, comprising 34 patients who were not able to do so. We found that the program was more effective in patients absent from work than in unemployed patients, TMT-B could predict work restoration and maintenance, and the frequency of rework program participation could predict work restoration but not work maintenance. Based on the findings, we propose ‘Yamashita’s criterion’ where a TMT-B completion time of 70 s is the cut-off point for work restoration. The present findings may provide useful evidence that could aid in the further development of rework program(s).